7 Июн 2021 в 19:42
37 +1
0
Ответы
1

To solve this equation, we first need to simplify the expression inside the parentheses:

(3 1/2 + (2/3))^2 = (7/2 + 2/3)^2
= (21/6 + 4/6)^2
= (25/6)^2
= 625/36

Now we can rewrite the equation using the simplified expression:

(625/36) * x + 3/18 = 5/18

Next, we can simplify the equation by multiplying both sides by 18 to get rid of the fractions:

625x/36 + 3 = 5

Now, we can move 3 to the other side of the equation:

625x/36 = 5 - 3
625x/36 = 2

To solve for x, we can multiply both sides by 36/625:

x = 2 * 36/625
x = 72/625

Therefore, the solution to the equation is x = 72/625.

17 Апр в 17:05
Не можешь разобраться в этой теме?
Обратись за помощью к экспертам
Название заказа не должно быть пустым
Введите email
Бесплатные доработки
Гарантированные бесплатные доработки
Быстрое выполнение
Быстрое выполнение от 2 часов
Проверка работы
Проверка работы на плагиат
Интересные статьи из справочника
Поможем написать учебную работу
Название заказа не должно быть пустым
Введите email
Доверьте свою работу экспертам
Разместите заказ
Наша система отправит ваш заказ на оценку 91 157 авторам
Первые отклики появятся уже в течение 10 минут
Прямой эфир